CHRISTOPHER MARLOWE'S “CARPE DIEM POETRY" - Eshmamatov Artur Bekmamat oʻgʻli (TADQIQOTLAR.UZ, 2024)
This article delves into Marlowe's use of carpe diem motifs in his works, examining how he grapples with the concepts of time, transience, and mortality. Through an analysis of key poems, we uncover the significance of carpe diem poetry in Marlowe's oeuvre and its broader implications for Renaissance literature.